THE CONCEPT OF SIMPLIFICATION OF CRIMINAL PROCEDURE: SCIENTIFIC VIEWS AND DOCTRINAL APPROACHES - С. Т. Алишаев (Ecominds Press, 2026)
The article discusses the scientific and theoretical foundations of the concept of simplification of the criminal process. The correlation of the categories "simplification", "optimization" and "procedural economy" is revealed, their common and distinctive features are revealed. Particular attention is paid to the legal nature of the simplification of criminal proceedings, as well as its limits in the context of the principles of fair trial, procedural guarantees and protection of human rights. The main doctrinal approaches to the institution of simplification of criminal procedure are analyzed and the need for its conceptual development in the national criminal procedure system is substantiated.
Keywords: Criminal procedure, simplification, optimization, procedural economy, fair trial, procedural form.